ASSESSMENT OF SELF-PERCEPTION AND SELF-ATTITUDES IN WOMEN’S RUGBY SEVENS ATHLETES - SURMEI-BALAN, Mihaela-Gabriela; COJOCARIU, Adrian; MARTINAȘ, Florentina-Petruța (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2025)
The purpose of the present study is to analyze the levels of self-perception among Romanian female Rugby Sevens players, both juniors and seniors, by identifying potential differences according to their performance level. We hypothesize that female Rugby Sevens players generally exhibit high levels of self-perception. Furthermore, we assume that differences in self-perception exist between club players and those competing for the national team. The study included 97 female Rugby Sevens players participating in the 2024 edition of the Romanian National Championship: 29 senior players with a mean age of 21.1 ± 4.8 years and 68 junior players with a mean age of 15.2 ± 1.5 years. Self-perception was assessed using the PAS Questionnaire: Perceptions and Self-Attitudes. Statistical analyses were performed with IBM SPSS Statistics 20, applying the Shapiro–Wilk test, Kolmogorov–Smirnov test, Frequencies, Independent-Samples T Test, and the nonparametric Mann–Whitney U test. The results indicate generally high levels of self-perception among female Rugby Sevens players, although medium and low values were observed on certain scales. Additionally, statistically significant differences were found between club players and national team players, both at junior and senior levels.